Empirical Examination of Stock Market Volatility : An International Comparison - Aggarwal, Shalini; Khurana, Simmi (Indian Journal of Finance, 2018)
The purpose of this paper was to investigate the market integration among the four selected BRIC economies namely Brazil, Russia, India, and China from January 2008 to August 2015. Johansen cointegration test was used to study the long term relationship between the four stock markets. Further, to ascertain the short term association, vector error correction model and impulse response function were used. The results showed that there existed one long run cointegrating relationship between the four stock markets under study. Although there was no long run causality among the four stock markets, but there existed short term causality running from Russian, Chinese, and Brazilan stock markets to the Indian stock market.